1.2(3b+5)=2 (2.4b-3.6) 3.2 (5x-1)=3.6x-9.4 -3 (2.1x-4)-4.2=1.2 (-5x+0.5)

1.2(3b+5)=2 (2.4b-3.6) 3.2 (5x-1)=3.6x-9.4 -3 (2.1x-4)-4.2=1.2 (-5x+0.5)
Гость
Ответ(ы) на вопрос:
Гость
1.2(3b+5)=2 (2.4b-3.6) 1,2*3b+1,2*5=2*2,4b-2*3,6 3,6b+6=4,8b-7,2 4,8b-3,6b=6+7,2 1,2b=13,2 b=13,2:1,2 b=11 3.2 (5x-1)=3.6x-9.4 3,2*5x-3,2=3,6x-9,4 16x-3,6x=-9,4+3,2 12,4x=-6,2 x=-6,2:12,4 x=-0,5 -3 (2.1x-4)-4.2=1.2 (-5x+0.5) -3*2,1x+3*4-4,2= -1,2*5x+1,2*0,5 -6,3x+7,8=-6x+0,6 6,3x-6x=7,8-0,6 0,3x=7,2 x=7,2:0,3 x=24
Не нашли ответ?
Ответить на вопрос
Похожие вопросы